PERANCANGAN SISTEM E-ARSIP MENGGUNAKAN SUBJECT FILING SYSTEM BERBASIS FRAMEWORK CODEIGNITER (STUDI KASUS STMIK MARDIRA INDONESIA) - Dinda Devianty; Rohmat Nur Ibrahim; Heri Wahyudi (Jurnal Computech & Bisnis (e-Journal), 2021)
STMIK Mardira Indonesia is one of the private universities in the city of Bandung. As an educational institution, STMIK Mardira Indonesia has a lot of important data, such as alumni data, student data, lecturer data, and other important data stored in filing cabinets. With the rapid development of information technology and continues to evolve until now. This can be proven by the many innovations and inventions that are simple to very complex. Such as Digital Archives or commonly referred to as E-Archives. Therefore, the design of the E-Archive system is very important because it can be seen from various aspects that can save important data or files.E-Archive System Design Using the Subject Filing System Method at STMIK Mardira Indonesia is a descriptive analysis method while the system development method uses the Object Oriented Analysis and Design (OOAD) method. The software used in making the E-Archive System Design Using the Subject Filing System Method at STMIK Mardira Indonesia is using the CodeIgniter Framework as a programming language and using MySQL as a database.As is E-Archive System Design Using Subject Filing System Method at STMIK Mardira IndonesiaThis can simplify the management of archiving alumni data, and computerized diploma data. The design of this E-Archive System can also provide information about the work of alumni after graduation. Keywords: E-Archive,Object Oriented Analysis and Design (OOAD), Codeigniter, MySQL, databases.DOI: 10.5281/zenodo.5784170